Influence of market orientation, product innovation and digital marketing on marketing performance in fashion MSMEs in Central Java Province - Yetti - Ashari; Winarto - Winarto; Isnaini - Nurkhayati (JOBS (Jurnal Of Business Studies), 2022)
Every year, micro, small and medium enterprises experience increasing development, business competition cannot be avoided. Micro, Small and Medium Enterprises (MSMEs) face various problems such as increasingly fierce market competition and also a lack of understanding of digital marketing. This affects the marketing performance of MSMEs. The purpose of this study is to analyze market orientation, product innovation, and digital marketing that affect marketing performance in fashion MSMEs in Central Java Province. The sample was determined using purposive sampling method. Data was collected by distributing questionnaires. Data analysis using multiple linear regression analysis method. The results show that market orientation, product innovation and digital marketing have a significant effect on marketing performance